The Relevance of Financial Information and Contents of the New Audit Report for Lending Decisions of Commercial Banks - Marina Trpeska; Atanasko Atanasovski; Zorica Bozinovska Lazarevska (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This research study examines the importance of financial information and information contained in the ISA's New Audit Report effective from 2016 for lenders as capital providers. We base our findings on a survey conducted in September of 2016 with corporate loan officers for medium-large corporate clients in Macedonia. The results show that the annual report of the company, except for the management report and notes to the financial statements, has consistently high importance and usability for respondents' decision making. Various accounting ratios related to liquidity, financial stability and profitability of the company are considered very important and regularly used in credit analysis. However, respondents were not consistent in their shared perceptions regarding high importance of projected profits and historical information on operating cash flows. All loan officers gave high importance to the information found in existent auditor's report format regardless of the form of expressed opinion. Also, information on key audit matters, additional information on going concern and related auditor's judgement, procedures related to fraud risk were considered of high importance. Lenders rated as less important the disclosure of the name of engagement partner, auditor's statement on independence and compliance with ethical requirements and the level of materiality used in the audit.
Keywords: M41; 650; importance of audit; new auditor's report; survey; lenders; lending decisions